Lysosomes and unfolded protein response, determinants of differential resistance of melanoma cells to vinca alkaloids. (27th February 2015) - Vincent, Laure‐Anais; Attaoua, Chaker; Bellis, Michel; Rozkydalova, Lucie; Hadj‐Kaddour, Kamel; Vian, Laurence; Cuq, Pierre
Abstract: On account of its strong ability to become chemoresistant after a primary response to drugs, malignant melanoma (MM) remains a therapeutic challenge. This study focuses on acquired resistance to vinca alkaloids (VAs) using VA‐resistant MM cell lines (CAL1R‐VCR, CAL1R‐VDS, and CAL1R‐VRB), established by long‐term continuous exposure of parental CAL1‐wt cells to vincristine (VCR), vindesine (VDS), or vinorelbine (VRB), respectively. Transcriptomic profiling usingrma andrdam methods led to distinguish two cell groups: CAL1R‐VCR and CAL1R‐VDS, CAL1R‐VRB, and CAL1‐wt.mgsa of the specifically altered genes in the first group evidenced the GO terms 'lysosomal lumen' and 'vacuolar lumen' linked to underexpressed genes, and 'endoplasmic reticulum (ER) stress response' associated with overexpressed genes. A specific reduction of lysosomal enzymes, independent of acidic vacuole organelle (AVO) turnover, was observed (LTG probe) in CAL1R‐VCR and CAL1R‐VDS cells. It was associated with the specific lowering of cathepsin B and L, known to be involved in the lysosomal pathway of apoptosis. Confirming gene profiling, the same groups (CAL1R‐VCR and CAL1R‐VDS, CAL1‐wt and CAL1R‐VRB) could be distinguished regarding the VA‐mediated changes on mean size areas and on acidic compartment volumes. These two parameters were reduced in CAL1R‐VCR and CAL1R‐VDS cells, suggesting a smaller AVO accumulation and thus a reduced sensitivity to lysosomal membrane permeabilization‐mediated apoptosis. In addition, 'ER stress response' inhibition by tauroursodeoxycholic acid induced a higher VA sensitization of the first cell group. In conclusion, lysosomes and unfolded protein response could be key determinants of the differential resistance of MM to VAs.